Grape rootstock - scion interactions on shoot growth and cane maturing
Interaction between the rootstock and scion varieties (clones) was examined. Berlandieri x Riparia T. K. 5BB, Berlandieri x Riparia T.5C being the most widely used varieties in Hungary, Fercal, Ruggeri 140 being recently used on special soil conditions ; Georgikon 28 a new established variety and Berlandieri x Riparia T. 8B GK 10 clone were the rootstocks used. The V. vinifera L. varieties were a clone of Italian Riesling and two new hybrids from the same cross population f ( Noble Italian Riesling X Ezerjó) X ( Noble Italian Riesling X Pinot Gris )